Teknik Field Trip dalam Meningkatkan Kemampuan Menulis Feature yang Berkearifan Lokal pada Siswa SMA - Nufus, Hayatun; Barkudin, Barkudin; Agustina, Juaidah (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
Writing features was still difficult for high school students, especially in expressing ideas by telling short, clear, and interesting facts. For that, we need the right technique in teaching features. One technique that is expected to help students be able to write features is the field trip technique. Therefore, the purpose of this study was to describe the application of the field trip technique in improving the ability to write features with local wisdom in high school students. The method used in this research is a classroom action research method. The action research process consists of a four-stage procedure, namely planning, action, development, and reflection. Based on pre-test data and two cycles, the use of field trip techniques can improve students' ability to write features. This increase can be seen in the achievement of the KKM, which reaches a value of 75 from the pre-cycle of 7 students or 41%, in the first cycle there are 13 students who have completed or 76%, then in the second cycle there are 17 students who have completed or 100%. Meanwhile, those who have not reached the KKM have decreased from pre-cycle by 59%, cycle I by 24%, and cycle II to 0%. For this reason, it is recommended that the field trip technique be applied in learning to write at the high school level and equivalent by providing texts that have elements of local wisdom.